Komposisi Jenis dan Distribusi Gastropoda pada Ekosistem Mangrove di Pulau Tunda, Kabupaten Serang Banten, Jawa Barat - Larasati, Chandrika Eka; Wahyudi, Rhojim (Jurnal Ilmu Kelautan Lesser Sunda, 2022)
Tunda Island is one of a group of islands located in the northern area of Banten Province. In the eastern and southern parts of Tunda Island, there is a mangrove ecosystem which is a habitat for various organisms, one of which is gastropods. In the mangrove ecosystem, some gastropods live on the roots, stems, and leaves of mangroves by sticking and climbing, clinging to dead wood, to the muddy ground. It is necessary to know the type composition and distribution of gastropods in the mangrove ecosystem found on Tunda Island, Serang Regency, Banten. Gastropod sampling was carried out on a 5 x 5 m2 plot at the lowest tide. All types of gastropods found in the plots were taken by hand. The gastropod samples obtained were then cleaned and put in a sample bottle, then given a 70% alcohol solution as initial preservation for further identification at the Laboratory of Dry Hydrobiology, Marine Science and Technology, FPIK, Bogor Agricultural University. There are 19 types of gastropods found in the mangrove ecosystem of Tunda Island from 11 families, including: Cerithidea cingulata, Telescopium telescopium, Terebralia sulcata, Terebralia palustris, Cerithium kobelti, Chicoreus capucinus, Coralliophila persica, Littoraria scabra, Mitrella puella, Xenorita plana. indica, Clea helena, Morula biconica, Phos senticosus, Fissilabia decollate, Monodonta canalifera, Imbricaria vanicorensis. Based on the index value of the diversity index (H') (0.06 – 0.21 < H'< 2.0), dominance (D) (0.03 – 0.19 < D<0.50) and uniformity (E) (0.03–0.13) obtained, the gastropods found in the mangrove area on Tunda Island with a low level of diversity.